High-throughput screening method for discovering CatSper inhibitors using membrane depolarization caused by external calcium chelation and fluorescent cell barcoding - Luque, Guillermina M.; Schiavi-Ehrenhaus, Liza J.; Jabloñski, Martina; Balestrini, Paula A.; Novero, Analia G.; Torres, Nicolás I.; Osycka-Salut, Claudia E.; Darszon, Alberto; Krapf, Dario; Buffone, Mariano G. (Frontiers in Cell and Developmental Biology, 2023)
The exclusive expression of CatSper in sperm and its critical role in sperm function makes this channel an attractive target for contraception. The strategy of blocking CatSper as a male, non-hormonal contraceptive has not been fully explored due to the lack of robust screening methods to discover novel and specific inhibitors. The reason for this lack of appropriate methodology is the structural and functional complexity of this channel. We have developed a high-throughput method to screen drugs with the capacity to block CatSper in mammalian sperm. The assay is based on removing external free divalent cations by chelation, inducing CatSper to efficiently conduct monovalent cations. Since Na+ is highly concentrated in the extracellular milieu, a sudden influx depolarizes the cell. Using CatSper1 KO sperm we demonstrated that this depolarization depends on CatSper function. A membrane potential (Em) assay was combined with fluorescent cell barcoding (FCB), enabling higher throughput flow cytometry based on unique fluorescent signatures of different sperm samples. These differentially labeled samples incubated in distinct experimental conditions can be combined into one tube for simultaneous acquisition. In this way, acquisition times are highly reduced, which is essential to perform larger screening experiments for drug discovery using live cells. Altogether, a simple strategy for assessing CatSper was validated, and this assay was used to develop a high-throughput drug screening for new CatSper blockers.